KORESPONDENSI PROTO MELAYU POLINESIA, BAHASA JAWA YOGYAKARTA DAN BAHASA INDONESIA - Nurhayati, Endang (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
This article is based on a research study focussing on correspondenceamong Proto Malay Polynesian (PMP, for short), the Yogyakarta Javanese dialect,and Indonesian. The research employed a top-down reconstruction analysis.The results of the analysis have indicated that PMP is reflected in theYogyakarta Javanese dialect with the retention of the vowels /a/, /i/, /u/, and /íª/ andthe consonants /b/, /p/, /m/, /t/, /n/, /k/, /K/, /l/, and /s/ and an innovation in thevowels /i/, /ey/, and /íª/ and the consonants /z/, /q/, /b/, /R/, /s/, /S/, and /D/ and thatPMP is reflected in Indonesian with the retention of the vowels /a/, /i/, /u/, and /íª/and the consonants /b/, /p/, /m/, /t/, /d/, /n/, /k/, /K/, /l/, /r/, and /s/ and an innovationin the vowel /i/ and the consonants /q/, /z/, /R/, /D/, /s/, and /S/.Keywords: correspondence, reflection: retention, innovation